PENGARUH KESADARAN LINGKUNGAN, PENGETAHUAN LINGKUNGAN DAN KEPEDULIAN LINGKUNGAN TERHADAP SIKAP SERTA DAMPAKNYA PADA NIAT BELI PRODUK HIJAU THE BODY SHOP DI KOTA PEKANBARU - Magdalena Sari Yulfita; Zulkarnain Zulkarnain; Jushermi Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aimed to see how environmental awareness, environmental knowledge,and environmental awareness affected attitudes and their impact on green productpurchase intentions at The Body Shop in Pekanbaru City. The population in this study isthe people in Pekanbaru City who know the existence of The Body Shop's green products.While the sample is 200 respondents who live in Pekanbaru City who know The Bodyshop's green products and are over 17 years old. Sampling used non-probabilitysampling method and purposive sampling technique. This research instrument uses aquestionnaire and data analysis method using a Structural Equation Model (SEM)approach based on Partial Least Square (PLS) using SmartPLS 3.0 software. The resultsshowed that environmental awareness, environmental knowledge and environmental carehad a significant effect on attitudes towards green products at The Body Shop inPekanbaru City. Then environmental knowledge has a significant effect on the purchaseintention of The Body Shop's green products in Pekanbaru City, but environmentalawareness and environmental care have no significant effect on the purchase intention ofThe Body Shop's green products in Pekanbaru City. And then attitude has a significanteffect on the intention to buy green products at The Body Shop in Pekanbaru City.Meanwhile, attitude mediates the influence of environmental awareness, environmentalknowledge and environmental awareness on purchase intention through attitudes togreen products at The Body Shop in Pekanbaru City. Keywords: Environmental Awareness, Environmental Knowledge, EnvironmentalConcern, Attitude and Purchase Intention of Green Products